PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS DI SMA NEGERI 9 KABUPATEN BATANGHARI - Wulan Mareta, Benar Sembiring (Universitas Batanghari Jambi, 2020)
Abstract This study aims to determine (1) to determine the results of learning values and student learning styles on economic subjects in class X IPS at SMAN 9 Batanghari Regency. (2) to determine the effect of learning styles on learning styles on student learning outcomes in economics class X social studies at SMA Negeri 9 Batanghari Regency. The results showed that (1) the learning style variable was in the good category with an average of 3.80 and the Respondent's Achievement Level (TCR) of 7.61, and two (2) there was no significant effect between learning styles of learning styles on learning outcomes Social studies class X students at SMA Negeri 9 Batanghari Regency. This is indicated by the value of t>> 0.294 <0.2000 (3) there is no significant effect between learning styles on learning outcomes of students of class X IPS in SMA Negeri 9 Batanghari Regency. Keywords: Learning Style, Learning Outcomes